PERANCANGAN DAN PEMBUATAN TEMPAT SAMPAH PINTAR MENGGUNAKAN ARDUINO UNO BERBASIS IOT - Mahendra, Zein Alvin Dian (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 1 No 01 (2021): September 2021, 2021)
Every year the environmental problems faced by the Indonesian people are environmental pollution due to the lack of public knowledge about waste management. As a result of the lack of awareness from the public, waste accumulates which can be a source of disease growth. Based on this problem, it is necessary to have a trash can that can sort organic waste, inorganic waste and metal waste to suit the type of waste and add an IoT (Internet of Things) function that can provide information when the trash can is full and the gas content in the smart trash can to avoid buildup. rubbish. This smart trash can prototype uses an Arduino UNO microcontroller as data processing. Proximity sensor, IR sensor, touch sensor and Rain Sensor to detect Organic waste, Inorganic waste and Metal waste. Servo to control bin door, maingate and positioner. Ultrasonic sensors to detect the height of garbage and gas sensors to detect gas levels in the trash and Nodemcu as monitoring  IoT(Internet of Things)